Oriented structure of short fiber reinforced polymer composites processed by selective laser sintering : the role of powder-spreading process - Chen, Hui (2021)
Short fiber reinforced polymer composites processed by selective laser sintering (SLS) generally show an oriented fiber structure, which leads to anisotropic properties of fabricated components. However, the formation mechanism of fiber orientation is barely investigated. In this study, the oriented structure of the carbon fiber/polyamide12 composites processed by SLS is characterized using the X-ray computed tomography, and the role of powder-spreading in formation of the fiber orientation is investigated by simulation using the discrete element method. The short fibers in the fabricated sample show preferred alignment along the spreading direction (X direction) and perpendicular to the building direction (Z direction), even with the orthogonal scanning path. The formation of fiber orientation is attributed to the powder-spreading process. During the powder-spreading process, the particle pile experiences a shearing flow along the building direction, where the higher the Z position, the faster the X-direction speed of the particle flow. Consequently, short fibers driven by the torque caused by the shearing flow gradually rotate and align to the spreading direction, leading to the anisotropy in the final products. The strength of the shearing flow can be tailored by adjusting the spreading parameters such as layer thickness, spreading speed and rotating speed of the roller. Potential approaches to tailor the fiber orientation during the powder-spreading procedure of SLS are discussed.